2018
DOI: 10.1590/0104-6632.20180353s20170032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Direct Photolysis, Electrooxidation and Photoelectrooxidation for Rhodamine-B Degradation

Abstract: The focus of this study is to evaluate the efficiency of oxidation processes in the treatment of a solution containing Rhodamine-B (RhB) used in various industrial applications. The advanced oxidation processes of electrooxidation (EO) and photoelectrooxidation (PEO) were used. At the same time, direct photolysis (DP) was also applied. Total organic carbon (TOC) reduction and color removal were evaluated. There was an efficient color removal when DP was performed, and the color removal efficiency was the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…In these experiments, we observed the growth of the 515 nm peak, further supporting the proposal that RCS participate in RhB degradation (Figure S11). The results are consistent with the EC-chlorine system where HClO plays an essential role during the degradation of RhB [30,60]. In a similar way, Baddouh et al ( 2018) have previously demonstrated the electrooxidation of Cl − to HClO at Ti/RuO 2 -IrO 2 anode.…”
Section: Rhb Dye Degradation Studiessupporting
confidence: 84%
“…In these experiments, we observed the growth of the 515 nm peak, further supporting the proposal that RCS participate in RhB degradation (Figure S11). The results are consistent with the EC-chlorine system where HClO plays an essential role during the degradation of RhB [30,60]. In a similar way, Baddouh et al ( 2018) have previously demonstrated the electrooxidation of Cl − to HClO at Ti/RuO 2 -IrO 2 anode.…”
Section: Rhb Dye Degradation Studiessupporting
confidence: 84%
“…[11][12][13][14][15] Electrochemical methods have been also employed to detect contamination of waste waters with rhodamine dyes or to degrade the contaminants. [15][16][17][18][19][20][21] Redox processes in aqueous supporting electrolytes can generate reactive oxygen 16,[18][19][20][21] and chlorine 17,18,[20][21][22] species. Such intermediates can strongly influence the electrochemical transformations of rhodamine molecules.…”
Section: Introductionmentioning
confidence: 99%